Sex alters impact of repeated bouts of sprint exercise on neuromuscular activity in trained athletes - Billaut, F.; Smith, K. (Applied Physiology, Nutrition, and Metabolism, 2009)
This study characterized the effect of sex on neuromuscular activity during repeated bouts of sprint exercise. Thirty-three healthy male and female athletes performed twenty 5-s cycle sprints separated by 25 s of rest. Mechanical work and integrated electromyograhs (iEMG) of 4 muscles of the dominant lower limb were calculated in every sprint. The iEMG signals from individual muscles were summed to represent overall electrical activity of these muscles (sum-iEMG). Neuromuscular efficiency (NME) was calculated as the ratio of mechanical work and sum-iEMG for every sprint. Arterial oxygen saturation was estimated (SpO2) with pulse oximetry throughout the protocol. The sprint-induced work decrement (18.9% vs. 29.6%; p < 0.05) and sum-iEMG reduction (11.4% vs. 19.4%; p < 0.05) were less for the women than for the men. However, the sprints decreased NME (10.1%; p < 0.05) and SpO2 (3.4%; p < 0.05) without showing sex dimorphism. Changes in SpO2 and sum-iEMG were strongly correlated in both sexes (men, R2 = 0.87; women, R2 = 0.91; all p < 0.05), although the slope of this relationship differed (6.3 ± 2.9 vs. 3.8 ± 1.6, respectively; p < 0.05). It is suggested that the sex difference in fatigue during repeated bouts of sprint exercise is not likely to be explained by a difference in muscle contractility impairment in men and women, but may be due to a sex difference in muscle recruitment strategy. We speculate that women would be less sensitive to arterial O2 desaturation than men, which may trigger lower neuromuscular adjustments to exhaustive exercise.